2019
DOI: 10.2147/copd.s226268
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Repetitive Saliva Swallowing Test Predicts COPD Exacerbation</p>

Abstract: IntroductionPredicting phenotypes at risk of chronic obstructive pulmonary disease (COPD) exacerbation is extremely important. Dysphagia is becoming recognized as one of these phenotypes. A convenient method of screening for dysphagia and COPD exacerbation risk is desired. The repetitive saliva swallowing test (RSST) is one of the least invasive dysphagia screening methods. We previously reported the possible relation between the RSST result and COPD exacerbation in a retrospective study. Based on this, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
14
0
4
Order By: Relevance
“…Details on patient background and dysphagia screening test results are explained in our previous study. 7 The patient background is shown in Table 1. There were 59 males (84.3%) and 11 females (15.7%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details on patient background and dysphagia screening test results are explained in our previous study. 7 The patient background is shown in Table 1. There were 59 males (84.3%) and 11 females (15.7%).…”
Section: Resultsmentioning
confidence: 99%
“…However, dysphagia in COPD is known to be multifactorial, and sarcopenia is only one of the risk factors. 7 Furthermore, tongue pressure is only one small part of the systemic musculature. In addition, the oral coordination needed for tongue pressure measurement was difficult to achieve in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that management of influencing factors can effectively improve patients' swallowing function 14 . Yoshimatsu et al [3,15,16] using Logistic regression to explore the influence factors of swallowing disorder in that age, the condition of teeth and depression are the influence factors of swallowing disorder and mentioned condition, the condition of disease and chronic diseases will affect its, however, these indicators cannot be directly measured variables (latent variable), conventional regression analysis method is difficult to deal with these factors, At the same time, regression analysis takes whether the independent variable has direct effect on the dependent variable as the estimation goal, and does not consider the internal interaction of the independent variable. Structural equation model is the synthesis of factor analysis and path analysis, which can make up for the deficiency of traditional methods.…”
mentioning
confidence: 99%